Tumor Interferon Signaling Regulates a Multigenic Resistance Program to Immune Checkpoint Blockade - Benci, Joseph L; Xu, Bihui; Qiu, Yu; Wu, Tony J; Dada, Hannah; Twyman-Saint Victor, Christina; Cucolo, Lisa; Lee, David S M; Pauken, Kristen E; Huang, Alexander C; Gangadhar, Tara C; Amaravadi, Ravi K; et al. (Cell, 2016)
Therapeutic blocking of the PD1 pathway results in significant tumor responses, but resistance is common. We demonstrate that prolonged interferon signaling orchestrates PDL1-dependent and PDL1-independent resistance to immune checkpoint blockade (ICB) and to combinations such as radiation plus anti-CTLA4. Persistent type II interferon signaling allows tumors to acquire STAT1-related epigenomic changes and augments expression of interferon-stimulated genes and ligands for multiple T cell inhibitory receptors. Both type I and II interferons maintain this resistance program. Crippling the program genetically or pharmacologically interferes with multiple inhibitory pathways and expands distinct T cell populations with improved function despite expressing markers of severe exhaustion. Consequently, tumors resistant to multi-agent ICB are rendered responsive to ICB monotherapy. Finally, we observe that biomarkers for interferon-driven resistance associate with clinical progression after anti-PD1 therapy. Thus, the duration of tumor interferon signaling augments adaptive resistance and inhibition of the interferon response bypasses requirements for combinatorial ICB therapies.